Rainbow matchings in Dirac bipartite graphs. Issue 2 (15th January 2019) - Coulson, Matthew; Perarnau, Guillem
Abstract : We show the existence of rainbow perfect matchings in μn ‐bounded edge colorings of Dirac bipartite graphs, for a sufficiently small μ  > 0. As an application of our results, we obtain several results on the existence of rainbow k ‐factors in Dirac graphs and rainbow spanning subgraphs of bounded maximum degree on graphs with large minimum degree.